Inhibisi Korosi Baja oleh Ekstrak Serbuk Gergaji Kayu dalam Medium Air Laut - Putri Hartika; Yerimadesi Yerimadesi; Hardeli Hardeli (Departemen Kimia FMIPA UNP, 2013)
The using of steel support building system in some productions in Indonesia, such us oil refineries, cooling systems production, shipbuilding and marine equipment. The sea is a corrosive environment so the metals which stay in the sea easy to corrosion. One of all effort to reduce the rate of corrosion of steel is the use of organic inhibitors such as tannins, nicotine and lignin. Wood sawdust is one natural ingredient that contains lignin. These compounds can complex with iron. This study aims to utilize wood sawdust extract as corrosion inhibitor of steel in medium of sea. Wood sawdust was extracted by using alkali method. The rate of corrosion and steel corrosion inhibition efficiency with wood sawdust extracts were determined by using the gravimetric method (the reduction of steel weight before and after corrosion). Based on the results of the study showed that the extract of wood sawdust can reduce the corrosion rate of steel in the medium of the sea with corrosion inhibition efficiency of 38.8% on 30 ppm the extract concentration. The analysis of steel surfaces using a stereo microscope with a magnification 40 times. It can seen the difference surfaces between coated steel and uncoated with wood sawdust extract in medium of the sea. Coated steel less rusty than uncoated.